Voice of a Leader: If you Truly Believe Children are our Future - the Future is Now! - Christian, Wayne (First Peoples Child & Family Review, 2010)
This paper is based on a speech by Chief Wayne Christian the Co-keynote speaker for the “Gathering and Sharing Wisdom Conference” held in Victoria BC October 6th & th, 2010. He shares the history of his community, their children and how state policies, legislation and laws have affected a way of life for his people. He illustrates through narrative the importance of re-learning our cultural practices. Chief Christian begins his account by quoting a historical approach remembered by many Indigenous people in which the government policy of the day sought to “Kill the Indian in the Child.” Chief Christian noted that First Nations people have resisted this policy, but importantly, he discussed how balance can be restored today for Indian children.